Pelaksanaan Restorative Justice Terhadap Pelaku Tindak Pidana Penganiayaan Anak Di Kepolisian Daerah Bali - Doni Darmawan Tikoalu; Rugun Romaida Hutabarat (LPPM Universitas Ekasakti Padang, 2024)
Law enforcement officials, particularly those in the Bali Regional Police, are undoubtedly concerned about the increase in juvenile criminal activity in Bali Province. The restorative justice approach which involves transferring is one of the options for managing criminal cases involving minors. The study's objective is to ascertain how the Bali Regional Police applies the restorative justice concept to cases involving child abuse. The research is of a descriptive character, and it is the empirical legal research. Primary data originates from police interviews conducted by the Bali Regional Police work unit, which specializes in managing juvenile crimes; secondary data is gathered from publications such as books, articles, and records. Qualitative data analysis is done and then presented in a descriptive manner. The outcomes demonstrated that the Bali Regional Police had applied the restorative justice concept in a very effective manner when it came to the crime of child abuse. The legal culture component in society has an influence on the barriers that the Bali Regional Police faces while attempting to implement the restorative justice principle in child abuse cases.